Cultural Values in the Film Barakati - Annisa Mutmainah; Dedi Warsana (Universitas Pendidikan Indonesia, 2021)
The film “Barakati” is a historical and adventure genre film that combines cultural elements from Buton Island and Yogyakarta. This film tells the story of an expedition involving a young archaeologist, a foreign journalist, a woman from Buton, and also someone who is a descendant of the Majapahit Kingdom. The method used in this study is a qualitative research method. Qualitative research methods are descriptive and analytical methods. In this study, a description of the results of observing the plot of this film was carried out which was then analyzed against the cultural values contained in the film